INDEK KEPUASAN MASYARAKAT TERHADAP PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PONOROGO - Patmini Patmini (Master of Public Administration, Universitas Slamet Riyadi, 2020)
The results of the study showed that the quality of service in the DukcapilOffice as a community service in making population document data is a quiteeffective strategy in increasing the awareness of population document datacompleteness. This can be seen from the moderate satisfaction of the communitytowards the quality of the service at the Dukcapil Department. Whereascommunity satisfaction with the quality of service at the Dukcapil Departmentturned out to have an impact on community satisfaction in Ponorogo Regency.Data from the questionnaire results are known that the community considers thequality of Population Administration services in the Dukcapil Department as afactor that is sufficient to influence community satisfaction. The above servicesturned out to also apply nationally, this is reflected in the majority of servicesprovided is a need that can be used as a completeness of the PopulationAdministration document of each citizen. The Reliability sub-variable indicator ofthe quality of information services requirements for making population documentshave the highest value, while the indicator of the quality of service for makingpopulation documents according to time has the lowest value. The Assurance subindicatorof community satisfaction with the ability of officers to answer each ofthe community's questions has the highest value, while the Reliability sub-variableof the community's satisfaction with the population documents in accordance withthe time has the lowest value.